Підривні соціальні технології у структурі гібридної війни - Рущенко, І. П.; Rushchenko, I. P. (Право і безпека. - 2015. - № 2 (57). - С. 12-16., 2015)
Предметом статті, присвяченої осмисленню подій російсько-української гібридної війни 2014–2015 рр., є «підривні соціальні технології» (авторський термін, скорочено – ПСТ), що можна розглядати як специфічний різновид соціальних технологій. Зазначено, що специфіка ПСТ у тому, що на території театру воєнних дій використовується тактика «керованого хаосу», розгортаються масові антиурядові акції під прикриттям тези щодо реалізації демократичних прав громадян. Агресор заздалегідь розробляє відповідні технології, створює управлінські контури, використовує ресурсну базу – соціальну, фінансову, організаційну. ПСТ мають слабкі місця і можуть бути зруйновані за умов, що протилежна сторона застосовує засоби ранньої діагностики, виявляє «критичні точки», відбувається координація зусиль державних інституцій та патріотичних кіл. Запропоновано залучати спеціалістів соціально-гуманітарного профілю для розв’язання проблем національної безпеки.

The article is devoted to understanding the events of Russian-Ukrainian hybrid war of 2014–2015. Specificity of the fourth generation war that was imposed to Ukraine is that in the first phase of active actions aggressor did not use weapons, but tried to reach the goals of the war, using the so-called «soft power». The object of the article is «subversive social technologies» (author’s term shortened – SST), which can be regarded as a specific kind of social technologies. Specificity of SST is that in the theater of war the tactic of «controlled chaos» is used, massive anti-government actions are spread undercover the thesis to implement democratic rights of citizens. Aggressor develop appropriate technologies beforehand, creates management contours, uses the resource base – social, financial, organizational. The analysis of events in the Crimea and eight regions of the East and South of Ukraine made it possible to single out a number of SST: – technology of arbitrary declaration of «people’s republic» within administrative units; – technology of «soft» seizure of power in the cities in favor of the aggressor; – technology of «human shield» using activists, women and even children; – technology of creation and use of criminal crowd; – technology «referendum». Example of Crimean events proves that the aggressor can actually achieve own goals without the direct use of weapons, if there is no clear understanding of the nature of SST and there is no plan of counter actions. SST have weaknesses and can be destroyed, if the other party uses the means of early diagnosis, reveals the «critical points», there is coordination of efforts of state institutions with patriotic organizations. The author offers to involve specialists of social and humanities to solve problems of national security that correspond international experience, namely US policy during World War II.

Предметом статьи, посвящённой осмыслению событий российско-украинской гибридной войны 2014–2015 гг., являются «подрывные социальные технологии» (авторский термин, сокращенно – ПСТ), которые можно рассматривать как особую разновидность социальных технологий. Указано, что специфика ПСТ заключается в том, что на территории театра военных действий используется тактика «управляемого хаоса», разворачиваются массовые антиправительственные акции под прикрытием тезиса о реализации демократических прав граждан. Агрессор заранее разрабатывает соответствующие технологии, создаёт управленческие контуры, использует ресурсную базу – социальную, финансовую, организационную. ПСТ имеют слабые места и могут быть разрушены при условии, что противоположная сторона использует средства ранней диагностики, выявляет «критические точки», существует координация усилий государственных институтов и патриотических сил. Предложено привлекать специалистов социально-гуманитарного профиля для решения задач национальной безопасности.
Rushchenko, I.P. (2015), “Subversive social technologies in the structure of a hybrid war” [“Pidryvni sotsialni tekhnolohii u strukturi hibrydnoi viiny”], Pravo i Bezpeka, No. 2, pp. 12–16.
Рущенко, І. П. Підривні соціальні технології у структурі гібридної війни // Право і безпека. - 2015. - № 2 (57). - С. 12-16.
Keywords: Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; Психологія. Рsychology. Психология; гібридна війна; підривні соціальні технології; «м’яка сила»; «п’ята колона»; тактика «керованого хаосу»; hybrid war; subversive social technologies; «soft power»; «fifth column»; tactics of «controlled chaos»; гибридная война; подрывные социальные технологии; «мягкая сила»; «пятая колонна»; тактика «управляемого хаоса»